2017
DOI: 10.1073/pnas.1707674114
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for rRNA 2′-O-methylation plasticity: Control of intrinsic translational capabilities of human ribosomes

Abstract: Ribosomal RNAs (rRNAs) are main effectors of messenger RNA (mRNA) decoding, peptide-bond formation, and ribosome dynamics during translation. Ribose 2'-O-methylation (2'-O-Me) is the most abundant rRNA chemical modification, and displays a complex pattern in rRNA. 2'-O-Me was shown to be essential for accurate and efficient protein synthesis in eukaryotic cells. However, whether rRNA 2'-O-Me is an adjustable feature of the human ribosome and a means of regulating ribosome function remains to be determined. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
293
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(323 citation statements)
references
References 43 publications
17
293
0
1
Order By: Relevance
“…Akin to METTL5, loss of the large subunit ribosomal protein Rpl38 doesn't affect global protein synthesis, but perturbs translation of a select subset of Hox mRNAs (43). Additionally, a repertoire of 2′-O-methylation sites in rRNA were identified to be subjected to variations and it was demonstrated that functional domains of ribosomes are targets of 2′-O-methylation plasticity (44). Moreover, the 28S rRNA A4220 is not always 100% methylated, e.g., it is about 50% level in HepG2 cells (9), suggesting that HepG2 cells may have ribosomes with and without m 6 A4220.…”
Section: Do Rrna Modifications Play a Role In Ribosomal Heterogeneity?mentioning
confidence: 99%
“…Akin to METTL5, loss of the large subunit ribosomal protein Rpl38 doesn't affect global protein synthesis, but perturbs translation of a select subset of Hox mRNAs (43). Additionally, a repertoire of 2′-O-methylation sites in rRNA were identified to be subjected to variations and it was demonstrated that functional domains of ribosomes are targets of 2′-O-methylation plasticity (44). Moreover, the 28S rRNA A4220 is not always 100% methylated, e.g., it is about 50% level in HepG2 cells (9), suggesting that HepG2 cells may have ribosomes with and without m 6 A4220.…”
Section: Do Rrna Modifications Play a Role In Ribosomal Heterogeneity?mentioning
confidence: 99%
“…Such mechanism within the ribosome is particularly important in the regulation of the gene expression [58]. Moreover, some functional domains of ribosomes have been shown to be targeted by the rRNA2'-O-me, inducing a modulation of the translation of mRNAs through plastic response [59]. Thus, such mechanisms suggest an indirect gene expression regulation through DNA methylation.…”
Section: Functional Effects Of Convergent Degsmentioning
confidence: 99%
“…The entire function of 2'-O-methylation remained unclear, which was limited to a research tool. The previous study suggested that Nm seemed to involved in immune response via mRNA 5' cap Nm sites, mRNA alternative splicing mediated by intron branch point, maintaining the secondary structure of rRNA, and regulating protein translation by interfering tRNA-mRNA or mRNA-rRNA interactions [5,6,11,14,21]. Based on our preliminary data shown in this article, the roles of Nm sites in cells were much more prevalent than we expected.…”
Section: Discussionmentioning
confidence: 56%
“…In the past few years, three high throughput Nm detection methods had been developed, which were 2'OMe-seq [12,13], RiboMethSeq [14][15][16] and Nm-seq [7]. The principle of 2'OMe-seq was based on the block of RNA reverse transcription at a low concentration of dNTPs.…”
mentioning
confidence: 99%